Magnetism : an investigation - Stringer, John. (New York : PowerKids Press, 2008)
This book explains how magnets work and how magnetism and electricity are connected and includes simple experiments.
Includes glossary.
Includes bibliographical references (p. 31) and index.
K-3
Accelerated Reader AR
Keywords: Magnets; Magnetism